PENGARUH KOMITMEN DAN MORAL REASONING TERHADAP KUALITAS AUDIT - Husnul Hasanah; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
AbstractThis research was conducted to analyze "the effect of commitment and moral reasoning on quality audit capabilities". The population in this study were 12 public accounting firms in Malang. The sample in this study were 7 public accounting firms in Malang. The sampling technique in this research is to use random sampling technique. The analytical method used is Multiple Linear Regression. the result obtained using a simple linear regression test y= 2,470+ 0.252 +ε , and the test from this study also used the test. Based on the results of simultaneous hypothesis testing, it shows that commitment and moral reasoning affect audit quality. The second result shows that commitment partially influences audit quality. The third result is that moral reasoning has a partial effect on audit quality. Keywords: Comitment, Moral Reasoning, Audit Quality